On the use of acoustic emission to identify the dominant stress/strain component in carbon/epoxy composite materials. (January 2021) - Kalteremidou, Kalliopi-Artemi; Aggelis, Dimitrios G.; Hemelrijck, Danny Van; Pyl, Lincy
Abstract: Acoustic Emission (AE) is casually employed for monitoring the mechanical behaviour of composite media as the amount of damage and the different fracture modes can be well characterised through the evolution of the AE characteristics. However, the sensitivity of the technique allows for more than just classification of the existing damage modes in composite materials. In the present paper, the limits of AE are further pushed as it is used to characterise the stress/strain field developing in composite laminates even before damage mechanisms become evident. In addition, the change of the strain field due to damage evolution during quasi-static and fatigue experiments, as monitored by real-time Digital Image Correlation (DIC), is depicted on the shift of the AE parameters. This is of great importance in cases that detrimental shear stresses are generated in the material, leading to important interlaminar delaminations and mechanical deterioration. AE can be used in this direction to predict the upcoming damage modes and to take the necessary measures to avoid final catastrophic failure by applying intermediate repair approaches. The examined material in this study is angle-ply Carbon Fibre Reinforced Polymer (CFRP) composite laminates consisting of different off-axis plies, in which different multiaxial conditions are generated due to the inherent anisotropy of composite materials. It is demonstrated that AE can identify the dominant stress/strain component rather than just the occurring damage mode even at early loading stages, before severe fracture influences the mechanical capacity of the material. v© 2020 The Authors. Published by Elsevier Ltd.